ChemInform Abstract: Electronic CD of Benzene and Other Aromatic Chromophores for Determination of Absolute Configuration. Issue 50 (10th December 2013) - Kurtan, Tibor; Antus, Sandor; Pescitelli, Gennaro
Abstract Review: 152 refs.